2019
DOI: 10.3892/etm.2019.8259
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin type 1 receptor regulates yes‑associated protein in vascular endothelial cells

Abstract: Aortic dissection (AD) is one of the most lethal cardiovascular diseases. Endothelial cell (EC) dysfunction serves an important role in AD progression. Angiotensin II (Ang II) is a key effector in cardiovascular disease development that acts through binding to angiotensin type 1 receptor (AT1R). Yes-associated protein (YAP) is well-known as a key mediator of cell proliferation and apoptosis. To determine whether AT1R and YAP influence EC proliferation or injury, human aortic endothelial cells were cultured und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 29 publications
0
9
1
Order By: Relevance
“…In contrast, in human aortic endothelial cells, Wang et al reported that AngII stimulation suppressed total YAP and increased p-YAP, as observed in other diseased conditions. 25 The contrary observation of increased total and p-YAP in our present study could be due to a SMC-specific YAP regulation by AngII. In support of our observation, an earlier study by Lin et al demonstrated that AngII infusion increased both total and phospho-YAP in the right common carotid artery in hypertensive rats and cultured rat thoracic aorta SMCs via AT1R activation.…”
Section: Discussioncontrasting
confidence: 96%
“…In contrast, in human aortic endothelial cells, Wang et al reported that AngII stimulation suppressed total YAP and increased p-YAP, as observed in other diseased conditions. 25 The contrary observation of increased total and p-YAP in our present study could be due to a SMC-specific YAP regulation by AngII. In support of our observation, an earlier study by Lin et al demonstrated that AngII infusion increased both total and phospho-YAP in the right common carotid artery in hypertensive rats and cultured rat thoracic aorta SMCs via AT1R activation.…”
Section: Discussioncontrasting
confidence: 96%
“…Cells were inoculated with three replicate sets per experimental group. We followed the CCK-8 method in our previous study (Wang et al, 2020).…”
Section: Cck-8 Assay and Flow Cytometric Analysismentioning
confidence: 99%
“…Endothelin (ET)-1 levels in supernatant from each group at the end of the 96 h treatment and in the mice serum from different group after 4 week feed were tested through competitive inhibition ELISA with ET-1 Antibody ELISA kit (USCN Life Sciences, Inc.), and interleukin (IL)-6 and matrix metallopeptidase (MMP)-9 in the cell solutions and mice serum were detected by double antibody ELISA with IL-6 ELISA Kit (USCN Life Sciences, Inc.) and MMP9 ELISA Kit (USCN Life Sciences, Inc.), respectively. We follow our previous research for ELISA (Wang et al, 2020).…”
Section: Elisa For Et-1 Il-6 and Mmp-9 Levels In The Supernatantmentioning
confidence: 99%
See 2 more Smart Citations